Localisation of a Global Brand: The Case Study of a Life Insurance Company in India - Swarup, Nisheeta (2007)
Due to the increasing globalization and homogenization of consumers' preferences in the world, global branding has become more widespread. Further globalization has opened up many choices for the consumer, with global brands being found in almost all locations around the world. The consumer is being placed in a position when a dilemma appears and they have to choose between familiar brands that they recognize and unfamiliar brands that hold a global appeal.